Proteomic and low-polar metabolite profiling reveal unique dynamics in fatty acid metabolism during flower and berry development of table grapes - Olmedo, Patricio; Vidal, Juan; Ponce, Excequel; Defilippi, Bruno G.; Pérez Donoso, Alonso G.; Meneses, Claudio; Carpentier, Sebastien C.; Pedreschi, Romina; Campos Vargas, Reinaldo (MDPI, 2023)
Grapevine development and ripening are complex processes that involve several biochemical pathways, including fatty acid and lipid metabolism. Fatty acids are essential components of lipids, which play crucial roles in fruit maturation and flavor development. However, the dynamics of fatty acid metabolism in grape flowers and berries are poorly understood. In this study, we present those dynamics and investigate the mechanisms of fatty acid homeostasis on ‘Thompson Seedless’ berries using metabolomic and proteomic analyses. Low-polar metabolite profiling indicated a higher abundance of fatty acids at the pre-flowering and pre-veraison stages. Proteomic analyses revealed that grape flowers and berries display unique profiles of proteins involved in fatty acid biosynthesis, triacylglycerol assembly, fatty acid β-oxidation, and lipid signaling. These findings show, for the first time, that fatty acid metabolism also plays an important role in the development of non-oil-rich tissues, opening new perspectives about lipid function and its relation to berry quality.